POLA PERTUMBUHAN DAN FAKTOR KONDISI IKAN SELUANG (Rasbora argyrotaenia) DI DANAU TELUK KENALI KOTA JAMBI - Maulida, Syafira; Gelis, Ester Restiana Endang; Lisna, Lisna; Nelwida, Nelwida; Arfiana, Bs Monica; Farizal, Farizal (Department of Fisheries, Animal Science Faculty, Universitas Jambi., 2025)
Teluk Kenali Lake is located in Teluk Kenali Village, Telanaipura District, Jambi City, with an area of approximately 30 ha, and has a water characteristic in the form of a basin. The main catch of fishermen in this lake is the seluang fish, which is popular with the community because of its taste and high economic value. This study used a purposive sampling method through direct observation of fishermen's catches. Samples were obtained from the catch of two fishermen using gillnet fishing gear with a mesh size of 1 inch during a 1-month study. The results showed that male seluang fish had an average length of 8.6 cm and an average weight of 4.9 g, with a b value in the length-weight relationship analysis of 2.88, a determination coefficient of 0.91, and a condition factor (K) of 1.75, indicating a less flat body. Female seluang fish had an average length of 9.04 cm and an average weight of 6.26 g, with a b value of 0.94, a determination coefficient of 0.18, and a condition factor of 1.99, indicating a less flat body. It was concluded that the growth pattern of male and female seluang fish was negatively allometric (b < 3), which means that length growth was more dominant than weight growth.